Pre-service Teachers' Cognition of Subject Teaching Knowledge: Dilemmas, Reasons and Strategies - GUO Xuejun; LIN Lin; LI Na (Jiaoshi jiaoyu xuebao)
Pre-service teachers' cognition of subject teaching knowledge consists of teachers' cognition of subject knowledge and teaching practice. Based on 27 reflection reports from 9 pre-service teachers, this study applies the qualitative research method to analyze their interpretation, restructuring, and presentation of subject knowledge, with the purpose of investigating the relation between teachers' cognition of subject knowledge and teaching practice, as well as the cognitive dilemma of pre-service teachers' subject teaching knowledge and its reason. It was found that if pre-service teachers fail to recognize the independence and professionalism of subject knowledge, it would be difficult for them to appropriately incorporate subject knowledge into teaching practice, which would result in the deficiency of subject knowledge in teaching practice. Therefore, the teacher educators should supplement relevant subject knowledge to help pre-service teachers form a rational, holistic, and comprehensive understanding of the subject teaching knowledge, while pre-service teachers should deepen and reorganize their cognition of the subject knowledge, adjust the perspectives of examining teaching content, and appropriately present subject knowledge in teaching practice.